COMMUNITY HEALTH WORKER SUPPORT AND HOME-BASED CARE PRACTICES FOR LOW BIRTH WEIGHT INFANTS: THE MEDIATING ROLE OF MATERNAL HEALTH LITERACY - Ayu Yuliani Sekriptini; Haryono Haryono; Oktia Woro Kasmini Handayani (Universitas Negeri Gorontalo, 2026)
Low birth weight (LBW) infants remain vulnerable to complications after discharge, making appropriate home-based care essential. This study examined the effects of Community Health Worker (CHW) Support on Home-Based Care Practices for LBW Infants, with Maternal Health Literacy as a mediating variable. This study advances previous research by positioning Maternal Health Literacy as an explanatory mediating mechanism that links CHW Support with Home-Based Care Practices, thereby providing a more comprehensive understanding of how community-based support contributes to maternal caregiving behavior after discharge. A quantitative cross-sectional survey was conducted among 250 mothers or primary caregivers of LBW infants selected through purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. CHW Support significantly and positively affected Maternal Health Literacy (β = 0.632; p 0.001) and Home-Based Care Practices (β = 0.232; p = 0.006). Maternal Health Literacy also had a positive and significant effect on Home-Based Care Practices (β = 0.415; p 0.001). Furthermore, Maternal Health Literacy significantly mediated the relationship between CHW Support and Home-Based Care Practices (β = 0.262; p 0.001). The model explained 40.0% of the variance in Maternal Health Literacy and 35.7% of the variance in Home-Based Care Practices. These findings indicate that CHW Support improves home-based care both directly and indirectly by strengthening mothers’ capacity to access, understand, evaluate, and apply health information. The findings contribute to a community-based neonatal care model by integrating Social Support Theory and the Health Literacy Framework in post-discharge care for LBW infants.